Optimization of high hydrostatic pressure processing for the preservation of minimally processed peach pieces - Denoya, Gabriela Inés (2016)
Consumers demand fresh-cut fruits, free from additives and with fresh appearance. However, the alteration caused by the tissue processing limits their shelf life. The aim of this work was to optimize the pressure level (from 400 to 600 MPa) and the holding time (from 1 to 9 min) of the high pressure processing (HPP) to achieve enzyme inactivation while preserving texture and color of minimally processed peaches. Peach cylinders were processed by combining dipping in organic acid solution, with vacuum packaging and HPP at room temperature. Results showed that higher pressure levels were more effective to inactivate enzymes and to preserve color than longer times. In addition, long treatments affected the microstructure and the texture of the tissues more seriously. Finally, a desirability study and a principal component analysis were performed. These showed that the optimal treatment would be 585 MPa and 1 min and that the best treatment of the ones studied was 600 MPa for 5 min.